دراسة مقارنة لتفاعل العنوان والصورة في الصحف السورية الرسمية والخاصة - جبور مازن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The media uses the image as a tool and a mean to touch the public opinion when it is broadcasted. Thanks to the technological development which enabled image global use and widespread. This in return, allowed image to contribute in the formation of the public opinion . This research aims to compare between image use in the official Syrian newspapers and the private ones, through analyzing the written titles and language accompanying to the image, and its significant role in supporting the addressed media message. The research displays the concept of media discourse and its importance, in addition to, image’s significance and types. Then, it looks in the analysis of images in the Syrian media discourse by focusing on the interaction and proportion between the image and the title in the written Syrian media. As well as, by a comparative study for image and title published in the next day announcement of the results of the Syrian parliament elections 2016 in the private Al-Watan newspaper and the official Al-Thwra newspaper. تستخدم وسائل الإعلام الصورة باعتبارها أداة ووسيلة لتحريك الرأي العام، ويعود الفضل في الاستخدام العالمي للصورة وانتشارها الكبير إلى التطور التكنولوجي، بحيث باتت تساهم بشكل مباشر في تشكيل الرأي العام. يهدف هذا البحث إلى المقارنة بين استخدام الصورة في الصحف السورية الرسمية والخاصة من خلال تحليل العناوين المكتوبة لغة المرافقة للصورة، وما لها من دور في تدعيم الرسالة الإعلامية. يعرض هذا البحث، مفهوم الخطاب الإعلامي وأهميته، كما يعرض أهمية الصورة وأنواعها، ثم يخصص الحديث للبحث في تحليل الصورة في الخطاب الإعلامي السوري، من خلال تسليط الضوء على مدى التفاعل والتناسب بين الصورة والعنوان في الإعلام السوري المكتوب بإجراء دراسة مقارنة للصورة والعنوان المنشورة في اليوم التالي لإعلان نتائج الانتخابات البرلمانية السورية للعام 2016، في جريدة الوطن السورية الخاصة وفي جريدة الثورة الرسمية.